KARAKTERISTIK PEREDAMAN GETARAN KONSTRUKSI MODEL JEMBATAN UNTUK PENGEMBANGAN SISTEM DIGANOSIS POLA GAGAL - Susilo Adi Widyanto; Achmad Widodo; Kamta Kamta; Agus Suprihanto; Faisal Yusuf Tornado; Canggih Nugroho (Teknoin, 2016)
In operation, the bridge structure is subjected to load variation both in the form of static load and dynamic load in variation of load intensity and frequency. In bridge structures made of steel structures, dynamic loading conditions can cause loosening of bolts, cracks and even structural failures. This paper describes the method of determining the damping bridge constant (c) by the logarithmic decrement calculation method of the vibration data generated by the impulse load. Furthermore the damping constant is used to calculate the vibration response equation of the structure along with the mass constant (m) and the stiffness of the structure (k). The mass constants are obtained by measurement whereas the stiffness constant of the structure is obtained by FEM modeling for open and closed structure models. The results of the analysis will be used to interpret the pattern of failed structures in the development of the diagnostic system. The calculation of damping constant for open and closed model is 0.07556 and 0.12513, while mass and stiffness constant for closed and open model model is 18 kg and 9 kg and 9523809.524 N / m and 183486.2 N / m for stiffness constant.